Why do gay people need norms? - Bogusławski, Marcin M. (Hybris, 2014)
The text critiques the approach to the norms characteristic of queer theory, developed in Poland by Jacek Kochanowski. In my view, the language of queer too strongly emphasizes the negative aspect of the norms, also unwittingly brings identity to human sexuality. Referring to the work of Michel Foucault's claim that gay people need norms in order to build both its own identity and the space of community life.